ORGANOCLAY FOR ADSORPTION OF BINARY SYSTEM OF POLLUTANTS FROM WASTEWATER (Journal of Engineering, 2011)
single and binary competitive sorption of phenol and p-nitrophenol onto clay modified withquaternary ammonium (Hexadecyltrimethyl ammonium ) was investigated to obtain theadsorption isotherms constants for each solutes. The modified clay was prepared fromblending of local bentonite with quaternary ammonium . The organoclay was characterizedby cation exchange capacity. and surface area. The results show that paranitrophenol isbeing adsorbed faster than phenol . The experimental data for each solute was fitted well withthe Freundlich isotherm model for single solute and with the combination of Freundlich-Langmuier model for binary system .